Marine fisheries management in the Eastern Central Atlantic Ocean - Takyi, R.; Addo, C.; EL Mahrad, B.; et al. (Ocean and Coastal Management, 2023)
Marine fishing is crucial to the socio-economy of West Africa fishery. However, the sector has many challenges, which have increased the call for an integrated approach that provides links among human needs, activities, changes in the state of the environment, and the resultant effect on ecosystem services for sustainable man agement in fulfilment of the Conservation on Biological Diversity and the Sustainable Development Goals. This study uses a socio-ecological framework (Drivers (D), Activities (A), Pressure (P), State (S), Impact (I) on welfare (W), and Response (R) as a Measure (M); DAPSI(W)R(M)) to assess the marine fishery sector of Ghana. Data were systematically sampled and analysed from vessel logbooks, fish manifests, observer reports, and relevant publications. Results show that Drivers, including livelihoods and revenue, food, and social status, contribute to industrial tuna and trawl fishing, and marine artisanal fishing activities. Where illegal fishing methods such as small mesh size nets (less than 25 mm), lights, poisonous substances, among others, are used. These activities have contributed to the pressures of selective fishing of juvenile and adult pelagic and demersal fish species. This has contributed to (changes in the State) the decline and vulnerability of Sardinella spp., and Engraulis encrasicolus, among others. The Impact on welfare includes Ghana becoming a net importer of marine species with increasing idleness of fishers due to reduced catch. Several management measures, including the Fisheries Act 625 of 2002 and Fisheries (Amendment) Regulations L.I. 2217 of 2015, and quotas in the tuna sector, among others, have been instituted to curb the effect of anthropogenic activities. Management measures, including influencing consumer behaviour for a sustainable fishery, enforcement, and data-driven management, have been recom mended, in response to the targets of the Sustainable Development Goals, the United Nations Decade of Ocean and the Convention on Biological Diversity.
Research Article
Keywords: Livelihoods; Adaptive management; Marine fishery; West Africa